Secure inpatient services: a needs assessment. (4th March 2014) - Hall, Ian; Yacoub, Evan; Boast, Neil; Bates, Robert; Stamps, Rebekah; Holder, Sarah; Beadman, Matthew
Abstract : Purpose: – The purpose of this paper is to complete a thorough needs assessment that would enable the development of a robust pathway of care for adults with a learning disability requiring secure care, and to assist commissioners to make informed planning decisions. Design/methodology/approach: – The paper identified people with a learning disability originating from London who were in secure care, and collected data about them. The paper used reference groups to inform the analysis. Findings: – The paper identified 249 people in secure services and was able to include 136 patients in the analysis. In all, 64 were in NHS provision and 72 in independent sector provision; 109 (80.1 per cent) were male and 27 (19.9 per cent) female; on average, patients were cared for 61.5 miles away from their homes; NHS patients were far closer to home; 69.1 per cent had a mild learning disability; 82.3 per cent had a history of violence; approximately one in six patients could not progress due to a lack of an appropriate ward, facility, resource and/or intervention. Practical implications: – Secure care for this population is a major public health issue. Many are placed a long way from home. Local services should be developed, and there should be sufficiently robust "step down" places for patients to be discharged to. Originality/value: – Systematic identification of the needs of a marginalised group to enable better more appropriate care pathways to be developed in the future.